Exercise during chemotherapy: Friend or foe? - Melanie Potiaumpai; Erica A. Schleicher; Ming Wang; Kristin L. Campbell; Kathleen Sturgeon; Kathryn H. Schmitz (Cancer Medicine, 2023)
Abstract Background A higher chemotherapy completion rate is associated with better outcomes including treatment efficacy and overall survival. Exercise may have the potential to improve relative dose intensity (RDI) by reducing the frequency and severity of chemotherapy‐related toxicities. We examined the association between exercise adherence and RDI and possible clinical‐ and health‐related fitness predictors of RDI. Methods Chemotherapy records were extracted from the electronic medical record for patients enrolled in the ENACT trial (n = 105). Chemotherapy completion was assessed using average RDI. A threshold of 85% was established for “high” versus “low” RDI. Logistic regression analyses were used to estimate the associations between the clinical‐ and health‐related fitness predictors of RDI. Results Patients with breast cancer (BC) had a significantly higher average RDI (89.8% ± 17.6%) compared with gastrointestinal cancer (GI) (76.8% ± 20.9%, p = 0.004) and pancreatic cancer (PC) (65.2% ± 20.1%, p < 0.001). Only 25% of BC patents required a dose reduction compared to 56.3% of GI and 86.4% of PC patients. Cancer site was significantly associated with RDI. Compared with BC, patients with GI (β = −0.12, p = 0.03) and PC (β = −0.22, p = 0.006) achieved significantly lower RDI. Every 2.72 unit increase in overall exercise adherence led to a significant 7% decrease in RDI (p = 0.001) in GI patients. Metastatic GI patients had a 15% RDI increase for every 2.72 unit increase in exercise adherence (p = 0.04). Conclusion Exercise is a supportive therapy that has potential to enhance chemotherapy tolerance and completion. The relationship between exercise adherence and RDI is influenced by factor such as cancer site and treatment type. Special attention must be paid to how exercise is prescribed to ensure that exercise adherence does not negatively affect RDI. Cancer site, exercise dosage, and multimodal interventions to address toxicities are key areas identified for future research.